2017
DOI: 10.1038/bmt.2017.187
|View full text |Cite
|
Sign up to set email alerts
|

Treatment intensity and symptom burden in hospitalized adolescent and young adult hematopoietic cell transplant recipients at the end of life

Abstract: Adolescent and young adult (AYA) oncology patients experience many physical and psychological symptoms at the end of life (EOL); however, data on these experiences for AYA patients that have undergone hematopoietic cell transplantation (HCT) remains sparse. We sought to investigate the characteristics of AYA patients aged 15 − 25 who received allogeneic HCT and subsequently died while inpatient at our institution between the years 2008 − 2014. A standardized data extraction tool was used to collect information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 33 publications
2
44
0
1
Order By: Relevance
“…Symptom Reporting. Parent proxy report (n = 13, 48%) was the most common method used to obtain information related to symptom experiences during the EOL period for children with cancer (Friedrichsdorf et al, 2014;Heath et al, 2010;Ilowite et al, 2018;Latha et al, 2016;Pritchard et al, 2008;Schindera et al, 2014;Theunissen et al, 2007;Tomlinson et al, 2011;Ullrich et al, 2010a;Ullrich et al, 2010b;von Lutzau et al, 2012;Wolfe et al, 2015;Zelcer et al, 2010) followed by medical chart review (n = 11, 41%; Bell et al, 2010;Beretta et al, 2010;Birtar et al, 2015;Hassan et al, 2018;Hechler et al, 2008;Hoell et al, 2017;Jagt-van Kampen et al, 2015;Kuhlen et al, 2016;Snaman et al, 2018;Veldhuijzen van Zanten et al, 2015;Ye et al, 2019). Of the studies that used parent proxy-report, 4 (31%) used a combination of parents', providers' and patients' reports (Ullrich et al, 2010a;Van Cleve et al, 2012;Wolfe et al, 2015;Zhukovsky et al, 2015).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Symptom Reporting. Parent proxy report (n = 13, 48%) was the most common method used to obtain information related to symptom experiences during the EOL period for children with cancer (Friedrichsdorf et al, 2014;Heath et al, 2010;Ilowite et al, 2018;Latha et al, 2016;Pritchard et al, 2008;Schindera et al, 2014;Theunissen et al, 2007;Tomlinson et al, 2011;Ullrich et al, 2010a;Ullrich et al, 2010b;von Lutzau et al, 2012;Wolfe et al, 2015;Zelcer et al, 2010) followed by medical chart review (n = 11, 41%; Bell et al, 2010;Beretta et al, 2010;Birtar et al, 2015;Hassan et al, 2018;Hechler et al, 2008;Hoell et al, 2017;Jagt-van Kampen et al, 2015;Kuhlen et al, 2016;Snaman et al, 2018;Veldhuijzen van Zanten et al, 2015;Ye et al, 2019). Of the studies that used parent proxy-report, 4 (31%) used a combination of parents', providers' and patients' reports (Ullrich et al, 2010a;Van Cleve et al, 2012;Wolfe et al, 2015;Zhukovsky et al, 2015).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…Most studies (n =16, 59%) used investigator-developed questionnaires (Heath et al, 2010;Hechler et al, 2008;Latha et al, 2016;Theunissen et al, 2007;Ullrich et al, 2010a;Ullrich et al, 2010b;von Lutzau et al, 2012) or validated instruments to obtain information about symptom experiences at EOL (Birtar et al, 2015;Friedrichsdorf et al, 2014;Ilowite et al, 2018;Rosenberg et al, 2016;Snaman et al, 2018;Tomlinson et al, 2011;Van Cleve et al, 2012;Wolfe et al, 2015;Zhukovsky et al, 2015). The PediQUEST Memorial Symptom Assessment Scale was the most common validated tool used (Birtar et al, 2015;Ilowite et al, 2018;Rosenberg et al, 2016;Wolfe et al, 2015;Zhukovsky et al, 2015).…”
Section: Symptom Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Rationales for this EOL pattern of care have been proposed, including the unpredictable pattern of clinical decline in patients with hematologic malignancies, clinicians' bias toward offering all possible treatments for these patients, and the small but finite possibility of cure for select patients [17]. Studies have similarly demonstrated that adults undergoing allogeneic HCT for hematologic malignancies use high levels of healthcare resources at EOL [18][19][20][21][22]. However, despite the exceedingly high risk of mortality in AL/MDS patients who relapse after allogeneic HCT, little data exist specifically examining the intensity of healthcare utilization broadly and at the EOL in this patient population, with the few existing studies reporting qualitative or limited data on small patient samples [23,24].…”
Section: Introductionmentioning
confidence: 99%